2018
DOI: 10.4172/2161-0460.1000412
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Circuit-Level Understanding of Hippocampal CA1 Dysfunction in Alzheimer's Disease Across Anatomical Axes

Abstract: The hippocampus has been a primary region of study with regards to synaptic and functional changes in Alzheimer’s disease (AD) due to its involvement in early stages, specifically area CA1. However, most work in this area has treated CA1 as a homogeneous structure comprised of uniform neural circuits. Yet, there is a plethora of evidence that CA1 varies in its structure and function across anatomical axes. Here I review the heterogeneity of the functional and circuit architecture of hippocampal area CA1 across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 88 publications
(99 reference statements)
1
34
1
Order By: Relevance
“…The latter is consistent with our previous observation reporting a downregulation of PARP-1 positive staining in the hippocampal CA1 region in AD compared to controls [22]. These results are also consistent with previous observations in which CA1- subiculum was found to be involved early in spatiotemporal progression of AD atrophy and hypometabolism, and postulated to be particularly vulnerable due to high synaptic output and metabolic demand [34]. In this study, we did not find a decrease in the percentage of PARP-1 positive nucleoli in the CA4 region in AD, in contrast to our previously reported findings.…”
Section: Discussionsupporting
confidence: 93%
“…The latter is consistent with our previous observation reporting a downregulation of PARP-1 positive staining in the hippocampal CA1 region in AD compared to controls [22]. These results are also consistent with previous observations in which CA1- subiculum was found to be involved early in spatiotemporal progression of AD atrophy and hypometabolism, and postulated to be particularly vulnerable due to high synaptic output and metabolic demand [34]. In this study, we did not find a decrease in the percentage of PARP-1 positive nucleoli in the CA4 region in AD, in contrast to our previously reported findings.…”
Section: Discussionsupporting
confidence: 93%
“…The hippocampus might have discrete functional domains along its regions and subregions that affect learning and memory processes, so region-specific differences could also be observed in the deterioration of the LTP during AD progression. Several studies have reported differences in LTP induction and amplitude within the dorsal and ventral parts of the CA1 region in rodents [22]. While some studies using Tg AD mouse models [6,7] have indicated the relevance of DG-related impaired LTP and memory deficits in the AD rodent brain, our data indicate that the CA1 region might be, at least, equally critical in the process of the memory decline in AD.…”
Section: Resultscontrasting
confidence: 49%
“…One circuit that might be important to evaluate is the projection from the lateral entorhinal cortex to the CA1 region of the HPC. The CA1 subregion shows intrinsic and circuit heterogeneity that may underlie the involvement of this structure in AD-associated behavioral pathologies (Masurkar, 2018); thus, subregional and circuit analyses have potential to identify specific anatomical substrates of alcohol’s impact on AD. Given the involvement of these brain regions in the onset of AD-like pathology, attenuating activity of this pathway may block or enhance disease state.…”
Section: Discussionmentioning
confidence: 99%